2017
DOI: 10.1038/s41598-017-03495-1
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying the signal of localized surface plasmon resonance sensing for the sensitive detection of Escherichia coli O157:H7

Abstract: Gold nanorods (Au NRs) based localized surface plasmon resonance (LSPR) sensors have been widely employed in various fields including biology, environment and food safety detection, but their size- and shape-dependent sensitivity limits their practical applications in sensing and biological detection. In our present work, we proposed an approach to maximally amplify the signal of Au NRs based LSPR sensing by coating an optimized thickness of mesoporous silica onto Au NRs. The plasmonic peaks of Au NRs@SiO2 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…When coated by silica, the surface charge of nanoparticles becomes negative at physiological pH due to the low PZC of silica, allowing for an opposite electrostatic adsorption [ 134 ]. Antibodies have been physisorbed to negatively charged silica-coated AuNR [ 135 ]. Here, again, no study on the long-term stability of the resulting antibody-AuNR bioconjugates was performed.…”
Section: Functionalization Methods Of Gold Nanorodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When coated by silica, the surface charge of nanoparticles becomes negative at physiological pH due to the low PZC of silica, allowing for an opposite electrostatic adsorption [ 134 ]. Antibodies have been physisorbed to negatively charged silica-coated AuNR [ 135 ]. Here, again, no study on the long-term stability of the resulting antibody-AuNR bioconjugates was performed.…”
Section: Functionalization Methods Of Gold Nanorodsmentioning
confidence: 99%
“…Most of the papers we review in this section deal with gold nanorods without silica coating. Indeed, up to now, only two examples of biosensors based on AuNR@SiO 2 have been reported in the literature [ 135 , 175 ]. Both of them involve antibodies as bioreceptors and in one of the cases, it was demonstrated that the presence of a thin SiO 2 shell not only provided a protective layer and increased the shelf life of the particles, but also improved the overall efficiency of the biosensor [ 135 ].…”
Section: Applications Of Aunrs In Lspr Biosensingmentioning
confidence: 99%
“…There have been reports that under some circumstance, a protective layer can enhance the gure of merit when coated with Au and SiO 2 . 65,76,77 Thus, we conclude that the 1-BT treatment not only succeeded in stabilizing the sensor but also lead to improvements in the gure of merit, 208.9 and 170.43 nm per RIU for the 17 and 22 nm thick AgLSPR sensors respectively. Fig.…”
Section: Him Observation Of Unprotected and Protected Mfon Lspr Sensorsmentioning
confidence: 72%
“…Localized surface plasmon resonance (LSPR) is an indirect method able to enhance SPR sensitivity [ 36 , 37 , 38 ]. The LSPR approach has been applied to label-free, real-time pathogen detection, and small, cost-effective LSPR biosensor systems have been constructed.…”
Section: Spr Methodsmentioning
confidence: 99%